2017
DOI: 10.1371/journal.pone.0180494
|View full text |Cite
|
Sign up to set email alerts
|

Network effects in environmental justice struggles: An investigation of conflicts between mining companies and civil society organizations from a network perspective

Abstract: This paper examines conflicts that occur between mining companies and civil society organizations (CSOs) around the world and offers an innovative analysis of mining conflicts from a social network perspective. The analysis showed that, as the number of CSOs involved in a conflict increased, its outcome was more likely to be perceived as a success in terms of environmental justice (EJ); if a CSO was connected to other central CSOs, the average perception of EJ success was likely to increase; and as network dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…al.., 2019), sectoral dynamics, such as conflicts over wind power (Avila, 2018), dams (Del Bene et. al., 2018, or mining (Aydin et. al.., 2017), or specific thematic concerns, such as multidimensional violence in central American conflicts .…”
Section: Comparative Statistical Political Ecology Based On the Ejatlasmentioning
confidence: 99%
“…al.., 2019), sectoral dynamics, such as conflicts over wind power (Avila, 2018), dams (Del Bene et. al., 2018, or mining (Aydin et. al.., 2017), or specific thematic concerns, such as multidimensional violence in central American conflicts .…”
Section: Comparative Statistical Political Ecology Based On the Ejatlasmentioning
confidence: 99%
“…These actors support local movements by providing experience, information, enhancing media attention and enabling a broader 'repertoire of contention' to include legal challenges [69,74]. A recent study found that when an environmental movement was connected to more civil society organisations, and especially when it was connected to more nationally or transnationally central civil society organisations, its outcome was more likely to be perceived as a success [75].…”
Section: Politics Of Scalementioning
confidence: 99%
“…In some cases, this can result in a loss of autonomy for local organisations, a need to alter strategies, ideological conflicts and identity loss [79]. Local movements need to be careful not to lose the grassroots while establishing links with supralocal organisations [75]. If there are inequities in coalitions, contradictory opinions on the appropriate values and arguments to use may mean that local environmental justice claims lose out to discourses introduced by more powerful supralocal organisations [80].…”
Section: Politics Of Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts can be filtered according to category, commodity, EJ Success, project status, conflict intensity, companies, EJ Organisations, and around 100 other fields (Martinez-Alier et al, 2016) and hence provide valuable insights, especially for activists and academics. To date, many scholars made use of the atlas to better understand the nature and dynamics of the ecological distribution conflicts (see, for instance, Aydin et al, 2017, Similar to the global pattern, Turkey has witnessed a growing number of environmental conflicts for the last three decades, following the aggressive neo-liberal policies of modernisation and industrialisation. Such policies were contested by the public at large through environmental mobilisations against mines, dams, thermal and nuclear power plants, and waste disposal.…”
Section: Introduction: Ecological Distribution Conflictsmentioning
confidence: 99%